The a to z of management skills - Hegde, Y.S.; Krishna, Rajeshwari (New Delhi : UBS Publishers', 1995)
Business
Keywords: Management skills; Industrial relation; Strategic management; Ethics in management; Communication; Time management; Corporate culture; Leadership